2012
DOI: 10.1080/00380768.2012.682045
|View full text |Cite
|
Sign up to set email alerts
|

Development of anaerobic bacterial community consisted of diverse clostridial species during biological soil disinfestation amended with plant biomass

Abstract: Biological soil disinfestation (BSD) using plant biomass incorporation is an effective method and a good alternative to chemical fumigants for controlling soil-borne plant pathogens. In this study the bacterial communities in pot soil treated with three different BSD conditions (without plant biomass and with Brassica juncea L. plants or bran of wheat, Triticum aestivum L.) were analyzed using mainly molecular techniques. Earlier dropping of redox potential of both biomass-treated soils indicated rapid develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 31 publications
7
58
0
Order By: Relevance
“…Since the incorporation of plant biomasses to the soil strongly enhanced growth of clostridial species as shown by the clone library analysis, VFAs might be produced by these anaerobic bacteria through decomposition of the biomass. These results coincided with the results of our previous study (Mowlick et al 2012). As mentioned below, we have 26 already isolated many strains of anaerobic bacteria from both B. juncea-and wheat-bran-treated soil used in this study and confirmed formation of acetate and butyrate as fermentation products for many of the isolates (data not shown).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Since the incorporation of plant biomasses to the soil strongly enhanced growth of clostridial species as shown by the clone library analysis, VFAs might be produced by these anaerobic bacteria through decomposition of the biomass. These results coincided with the results of our previous study (Mowlick et al 2012). As mentioned below, we have 26 already isolated many strains of anaerobic bacteria from both B. juncea-and wheat-bran-treated soil used in this study and confirmed formation of acetate and butyrate as fermentation products for many of the isolates (data not shown).…”
Section: Discussionsupporting
confidence: 81%
“…Besides, fatty acids like acetate or butyrate produced by these bacterial groups were supposed to contribute to pathogen inactivation (Momma et al 2006). These acids were actually detected in the BSD soil (Mowlick et al 2012), and it was strongly suggested that acetate, butyrate or other substances could be the products of the clostridial groups responsible for the suppression of some soil borne pathogens. Thus, it seems that proliferation of clostridial species in BSD treated soil may be important to make the treatment more effective.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations